A comprehensive FRT strategy based on individual arm capacitor voltage control for MMC in hybrid AC/DC distribution grids - Yu Chen; Zhen Wang; Minghao Wen; Xianggen Yin (International Journal of Electrical Power & Energy Systems)
Due to the wide application of modular multilevel converters (MMCs) in hybrid AC/DC distribution grids, enhancing the fault ride-through (FRT) capability of MMC is essential to improve the reliability of the hybrid AC/DC distribution grids. In this paper, an individual arm capacitor voltage control based comprehensive FRT strategy is presented. To balance the active power transmitted in each arm, an individual arm capacitor voltage control (IACVC) method is presented to regulate arm capacitor voltage stable to their reference. The decoupled control for positive pole and negative pole is achieved. Besides, an improved arm current references calculation (ACRC) method is proposed. During pole-to-ground (PTG) fault, the current of the fault pole is reduced to 0, and the healthy pole still transmit rated active power with rated voltage. In addition to, the adverse effects of AC side voltage imbalance are eliminated. The presented control strategy is verified by simulations and experiments on a MMC prototype.